2014
DOI: 10.1155/2014/686474
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Nickel and Tin Additives on the Microstructural and Mechanical Properties of Al-Zn-Mg-Cu Alloys

Abstract: The effects of nickel and nickel combined tin additions on mechanical properties and microstructural evolutions of aluminum-zinc-magnesium-copper alloys were investigated. Aluminum alloys containing Ni and Sn additives were homogenized at different temperatures conditions and then aged at 120°C for 24 h (T6) and retrogressed at 180°C for 30 min and then reaged at 120°C for 24 h (RRA). Comparison of the ultimate tensile strength (UTS) of as-quenched Al-Zn-Mg-Cu-Ni and Al-Zn-Mg-Cu-Ni-Sn alloys with that of simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…that the YS increase linearly with the increasing Si content. The increasing YS with the increasing Si content in the aged condition are also due to the presence of intermediate phase Al 3 Ni. Figure 18 shows the %elongation vs. wt % Si plot for the Al-0.1Mg-0.35Ni- (4,6,8,10) wt %Si alloy combination in the aged condition.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…that the YS increase linearly with the increasing Si content. The increasing YS with the increasing Si content in the aged condition are also due to the presence of intermediate phase Al 3 Ni. Figure 18 shows the %elongation vs. wt % Si plot for the Al-0.1Mg-0.35Ni- (4,6,8,10) wt %Si alloy combination in the aged condition.…”
Section: Resultsmentioning
confidence: 94%
“…Wear rate results Figure 19 shows the wear rate vs. wt % Si plot for Al-0.1Mg-0.35Ni- (4,6,8,10) wt %Si alloys in the aged condition. The wear rate was found to decrease with the increasing Si content and this behaviour was attributed to the formation of an intermediate phase Al 3 Ni. Figure 20 shows the wear rate vs hardness plot for the Al-0.1Mg-0.35Ni- (4,6,8,10) wt %Si alloys in the aged condition.…”
Section: Tensile Test Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In the Ni-containing alloys, Al3Ni phase is formed and acted as strengthening phase due to its high values of Young's modulus (116e152 GPa), hardness (HV0.01 ¼ 5130 MPa) and tensile strength (2160 MPa) [35,36], while the rigid Al3Ni compound is substantially inert in the alloy and acts as hard pinning points restraining dislocation motion which can affect the strength and elongation of Al alloys. Meanwhile, according to the discussion above, the amount of eutectic melt would increase, thus the initial shrinkage porosity can be refilled and healed.…”
Section: Fractured Surface and The Microstructure-properties Relationshipmentioning
confidence: 99%
“…Recently, Ni was found as a potential element capable of achieving these goals. The addition of Ni in Al alloys can increase the strength at room or elevated temperatures [30e36], which have been widely confirmed in Al-Si [30e33], AleMgeSieMn [34], Al-Si-Cu-Mg [35] and AleZneMgeCu [36] alloys. Meanwhile, Belov et al [37e39] analyzed the equilibrium phase diagram of AleZneMg-(Cu)eNi alloys using Thermal-Calo software, and found that Ni only exists in the form of Al þ Al3Ni eutectics.…”
Section: Introductionmentioning
confidence: 97%